ULAMA’S PUBLIC IMAGE IN ONLINE MASS MEDIA FOLLOWING THE CANDIDACY OF KH. MA’RUF AMIN - Isroqunnajah, Isroqunnajah; Thoyib, Muhammad Edy (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
Ulama plays various roles in the society, including as a social, economic, or cultural broker. However, when it comes to politics, ulama is sometimes only viewed as a magnet to attract electoral votes. This paper examined the representation of ulama in the media upon the nomination of KH. Ma’ruf Amin as Jokowi’s VP and aimed to shed a light on the extent such a representation could lead to the ulama’s image shift, by taking al-Mawardi’s concept of leadership into account. Considering the nature of the data, this study employed a descriptive-qualitative paradigm which attempts to produce descriptive information. The data; news texts were taken from four online media were collected through intensive reading and note-taking, while for social cognition purpose, the data were taken from student press activists and collected through a semi-structured interview. The results show that all the media under investigation employed a positive presentation upon KH. Ma’ruf Amin’s nomination by using various discursive strategies, such as presenting religious as well as political career background (authority), showing the burdens that imply a negative representation of others, and incorporating the numerical data to intensify the positive image being framed. Therefore, through those discursive vehicles, KH. Ma’ruf Amin’s image of leadership is solely projected in two qualities: religious authority and ability to manage public affairs.